Independecy Of Qualitative AuditRegarding The Audit Firm Size - Maqellari, Majlinda; Salko, Drini (European Scientific Journal, ESJ, 2016)
During the late 1970’s, regulators and small audit firms believed that the size of the audit firm did not affect audit quality. There is some criticism that the large accounting firms should not be arbitrarily distinguished from all the other Certified Public Accountants firms. De Angelo (1981) argues that consumers can use size as a measure of audit quality. This paper reports interview evidence on audit materiality and the answers to the variables regarding the size of the companies which is audited and the size of auditing company. Significant findings from the research interviews are Focus- Groups Questionnaires as a Method of Collecting Qualitative Data, in our case the group being the 215 Certified Public Accountants from Authorized Accountant Experts Institute, Albania. We want to bring out the Albanian auditor characteristic in assessing the qualitative audit, that is not depent on the size of the company who is audited or on the size of the auditing company. The result of the study can have significant implication for Authorized Accountant Experts Institute and the Quality Audit Control, which takes place once every five years for the experts on the field and for the young experts, it takes place once every two years.